Caries Prevalence in 12-year-old Children of Isfahan City Expressed by the Significant Caries Index - Sh - Javadinejad; M Karami; HR Azizi (Isfahan University of Medical Sciences, 2006)
Introduction: The Significant Caries (SiC) has been defined to determine dental caries for different societies by Word Health Organization. The good of present study was to evaluate Sic in 12-year-old students in city of Isfahan and make a comparison with dental caries risk factors.Methods and Materials: This was a descriptive cross sectional study. Three hundred and forty students, 12-year-old from Isfahan city were examined according to SiC Index by means of mirror and explorer. Risk factors and decay were evaluated recorded in separate check list. Findings were analyzed by Chi-square and SPSS soft ware.Results: The mean DMFT for all students were 2.4 and SiC Index was 4.6, which were directly related to factors such as regular brushing, parents' educational level, mothers' occupation families income, consump-tion of sweets, number of children in the family.Conclusion: SiC Index in 12-year-old students in Esfahan city was far from ideal SiC Index determined by World Health Organization which is 3. Therefore more attention to this group of student is recommended.